Socialization of bullying prevention for children at Aisyiyah PRA Panggungharjo III, Sewon, Bantul - Senja Yustitia; Wulan Widyasari (Universitas Muhammadiyah Magelang, 2024)
Indonesia ranks fifth among countries with the highest percentage of students experiencing bullying, according to data from the 2018 Programme for International Student Assessment (PISA). Approximately 41.1% of students in Indonesia reported being victims of bullying, a significant figure considering the severe impact of bullying on mental health, individual productivity, and the core values of education and humanity. In response to this issue, a community service program focusing on the socialization of bullying prevention among children was conducted at Aisyiyah PRA Panggungharjo III Sewon Bantul. The program aimed to enhance the understanding of Aisyiyah members, particularly mothers, to enable them to act as key agents in breaking the cycle of bullying through active roles in their families and communities. The program involved a series of stages, including preparation, socialization sessions featuring material presentations and interactive discussions, and evaluation through pre- and post-tests. The evaluation results demonstrated an increased understanding and awareness of bullying among participants, as reflected in the improved post-test scores compared to the pre-test.